The Evolution of Taipei's Music Industry: Cluster and Network Dynamics in the Innovation Practices of the Music Industry. (February 2014) - Lin, Cheng-Yi
This paper aims to explore the spatial and organisational dynamics of innovation activities in the evolution of cultural industry using Taipei's music industry as a case study. The existing literature has emphasised that innovation and creativity are driving the evolution of the cultural industry as a result of the spatial proximity effect generated by production systems. However, few studies have examined the innovation practices of the cultural industry resulting from interactive relationships between the urban cluster environment and the mobilisation process of project networks. An evolutionary perspective is used to illustrate how the cluster and network elements of the music industry are intertwined in innovation practices within the Taipei context. As a contribution to the cluster–network debates, this paper argues that the innovation dynamics of Taipei's music industry are a hybrid feature of Taipei's cluster environment and the strategic competencies of music project networks rather than the local cluster effect. In conclusion, a different trajectory for the evolution of Taipei's music industry is presented. Additionally, this dynamic process between cluster and network makes Taipei a hybrid creative platform that is an active element in the cultivation of the innovative competencies of Taipei's music producers and related workers.